DEVELOPMENT OF MANAGEMENT RESOURCE POTENTIAL OF AGRICULTURAL ENTERPRISES - Воловик, Д. В. (Scientific Progress & Innovations, 2014)
It has been determined that the effective management of the resource potential of agrarian enterprises should be a flexible system that will adapt to the market conditions and to ensure the overall development of the company. We analyzed the resource potential of the agrarian enterprise and offered the main directions of forming a system of efficient management of resource potential, for the development and implementation of which we have to achieve a high level of information and analytical support of management, which is essential for the development of the agrarian sector.